Analisis Pengaruh Mekanisme Good Corporate Governance terhadap Praktek Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2005-2007 - Setiawan, Teguh (Widya Mandala Surabaya Catholic University, 2009)
Earnings management is management intervention in financial statement reporting process, aimed to increase managernent's wealth personally and/or increase value of the firm. Earnings management is a factor that could reduce Financial statement credibility, increase bias, and prevent stakeholders .from believing profit values. Consistent good corporate government implementation is indicated could increasing financial statement quality and reduce earnings management activities. This research purpose is to find out whether corporate governance mechanisms, consists of institutional ownership, managerial ownership, proportion of independent board of commissioner, board of director, and audit committee, influence earnings management. The object of this research is manufacturing companies listed in Indonesian Stock Exchange in 2005-2007. There are ninety six companies selected with purposive sampling techniques and data was analyzed using multiple linier regression. The results show that proportion of independent board of commissioners and audit committee variables influence earnings management partially and significantly. Institutional ownership, managerial ownership, and independent board of commissioner’s variables didn't influence earnings management. Simultaneously, good corporate governance mechanisms influence earnings management significantly.